KONDISI SANITASI RUMAH DAN PERILAKU PENGHUNI (Studi KasusDi Pemukiman Sawahpulo RW11 Kelurahan Ujung Kecamatan Semampir - Yosi Arteri Rosalina; Umi Rahayu; Suroso Bambang Eko (Poltekkes Kemenkes Surabaya, 2014)
Healthy homes can be viewed from its basic sanitary conditions, construction, and the properbehavior of their occupants. The facts indicated that there are homes that do not have latrines, wastedisposal facility, open sewerage system, windows are rarely opened, increasing the risk of diseaseinfection and health problems to the community. The purpose of this study was to assessand determinethe sanitary conditions and the behavior of occupants in Sawahpulo RW 11 at Ujung village, SemampirSubdistrict, Surabaya.Employing a descriptive method, large sample of 92 houses were selected using a proportionalrandom sampling. Data collection were carried out using interviews and observation sheets. Respondentsin this study were housewives, that have been collected and subsequently tabulated, and discussed withreference to the Minister Regulation 829 / Menkes / SK / VII / 1999 on Health Requirements forResidential area .Results of the study on 92 homes showed that, 39 homes (42.3%) were in violation of basicsanitation facilities. Home components of 75 houses homes were not eligible (81.6%). In terms ofoccupant density, 35 homes (38%) were in violation of the standard. Regarding behavior of occupants, 90people (97.8%) were found to be unsatisfactory. The sanitary condition of the houses in as much as 8home (8.7%) have met the designated requirements while in the other 84 homes (91.3%) the conditionwere below standard. In the maintenance of sanitary conditions home dwellers have done poorly asshown by 79 people (85.9%).It is recommended to the Pegirian health center to initiate counseling on environment associateddiseases, initiate activities such as training on making handicrafts made from recycled plastic wastes andhow ro make compost. Public toilet facilities should be improved by installing doors, erect separator wallson each latrine unit and to provide water reservoirs for comfortable use, maintenance of latrines should bedone by scheduled teams. For the People should engage in the maintainenance of basic hygiene andsanitation facilities, home repair, improve basic sanitation facilities and repair damaged components.Change the behavior of the inhabitants in order to care more about the sanitary conditions of their ownhome and its environment and to provide information about healthy home quality.